Analisis Valeu For Money Dalam Meningkatkan Mutu Pelayanan Politik Pada Program Pembinaan Atlet KONI Asahan - Irma Chairani Tambunan; Zuhrinal M. Nawawi (ManBiz: Journal of Management and Business, 2022)
Value for Money is a performance indicator in a public sector that provides information on whether the budget (funds) provided provides a certain value for the community. The indicators referred to in this case are economic, efficient, and effective. Measuring athlete satisfaction with the services provided by KONI Asahan was carried out on 25 athletes in the Muaythai sport. This study aims to analyze Valur for Money in improving public services at the Asahan Indonesian National Sports Committee (KONI) in the design of athlete development with Valur for Money analysis. The measurement of athlete satisfaction with the services provided by the Indonesian National Sports Committee (KONI) Asahan is carried out by means of the IKM (Community Satisfaction Index). The results of the study show that all budget funds financed by the government have been used properly through the allocation of funds for coaching athletes and coaches. Keywords: Service, Value for Money, Athlete